Influence of selected retardants on the quality of winter wheat grain - Leszczyńska, Danuta (Polish Journal of Agronomy, 2019)
Growth regulators, or retardants, play a significant rolein the crop protection system, minimizing the risk of lodging. Thephenomenon of lodging contributes to qualitative losses and deteriorationof grain quality. In this paper, the effect of retardanttype, its rate and date of application, on selected quality featuresof winter wheat grain was evaluated.The study was carried out at the IUNG Experimental Stationin Osiny with winter wheat cultivar ’Roma’, grown after rootcrops. The experiment was conducted on the soil of the good ryecomplex. The three-year study was conducted using the methodof randomized split-plot with a control treatment, in four replications.The formulas of retardants (Cycocel 460 SL - chlormequatand Terpal C 460 SL - chlormequat + ethephon), application date(full tillering and first and second node stage) and application rate(maximum and minimum recommended by the Institute of PlantProtection) were the test factors.The reaction of wheat to the examined factors depended onthe type, rate and timing of retardant application. Statisticallysignificant differences in grain glassiness, gluten quality and theactivity of amylolytic enzymes, were found vs. the values of thecontrol sample. The application of retardants had no statisticallysignificant effect on grain bulk density, ash content and total proteinand gluten content.